Commitment to Islam in Kazakhstan and Kyrgyzstan: An Item Response Theory Analysis - Himelfarb, Igor (The international journal for the psychology of religion, 2016)
Worthington conceptualized a model of religiosity assessment. The dimensions of the model include Religious Norms, Religious Doctrine, and Authority of Leaders. A 10-item scale for Islamic religious assessment was constructed and administered in Kazakhstan and Kyrgyzstan. First-order factor analysis conducted on the 10 items of the religiosity scale revealed factorial structure corresponding to Worthington’s model. A second-order factor analysis assured 1 underlying latent trait. Two-parameter logistic item response theory models were fit to responses collected in Kazakhstan and Kyrgyzstan. Results supported psychometric soundness of the instrument. The items on the scale revealed excellent discrimination properties between the populations of high and low religious commitment. The study offers a short, practical scale for assessment of commitment to Islam in Central Asian countries.